Strategi Pembelajaran Pendidikan Agama Islam pada Anak Autisme di SLB Indonesia - Rubianti, Elen Aleni; T, Sutaryat; Hanafiah, Hanafiah (Lembaga Yasin AlSys, 2023)
Special education for children with developmental disabilities is described as a form of education provided either in specialized schools or inclusive schools. Law of the Republic of Indonesia Number 20 of 2003 clearly states that every citizen has the right to the highest possible education. Citizens who have physical, emotional, mental, intellectual, and social disabilities are also entitled to special education. The purpose of this study is to determine the Learning Strategies of Islamic Religious Education in Children with Autism in SLB Indonesia. This research method uses a qualitative type of research with a transcendental phenomenological approach (Moustakas, 1994). This study was conducted to explore more information about teachers' experiences in implementing learning for children with autism. The results of this study show that in the implementation of learning, two-way communication strategies, adequate experience, teaching skills, creativity, and teacher innovation skills are competencies that teachers must have, especially in inclusive schools. This competency component is important for teachers before entering inclusive schools. The success of character education, especially for children with autism, requires strong collaboration in the environment, namely schools and teachers. School policies can take the form of curriculum, infrastructure, and facilities. The results of the description and analysis of data on the Learning Strategy for Islamic Religious Education in Autistic Children in SLB Indonesia, it can be concluded that the learning strategy used in Indonesia uses basic strategies in general that are taught to autistic children. Using repetition strategies, and practice directly to learners, so that learners can understand learning well.